Manajemen Kurikulum dalam Meningkatkan Mutu Pendidikan (Studi Kasus di SD Negeri Puncak 2) - H. Soro, Suharyanto; Suherman, Maman; Rachmawati, Sisca; Ardiansyah, Yudah (LP. Ma'arif Janggan Magetan, 2024)
This study aims to analyze curriculum management strategies in improving the quality of education at SD Negeri Puncak 2. Using qualitative methods with case study approach through observation, in-depth interviews and document analysis. The research subjects included the principal, teachers and related staff involved in curriculum planning, implementation and evaluation. The results show that the curriculum management strategies implemented include three main aspects: participatory curriculum planning, student needs-based curriculum implementation, and continuous curriculum evaluation. In planning, the involvement of all stakeholders, including teachers and parents, ensures that the curriculum is relevant to the local context. In the implementation phase, the use of active learning methods and the integration of technology are key factors in creating an engaging and effective learning process. Evaluation is done through regular monitoring and reflection on student learning outcomes, which are used to improve future learning strategies. The study also identified some challenges, such as limited resources and training needs for teachers, that need to be addressed to improve the effectiveness of this strategy. Using a holistic approach, curriculum management at SD Negeri Puncak 2 has had a positive impact on the quality of education, particularly in improving student learning outcomes.